The impact of return policies on consumers' online shopping intentions in Ho Chi Minh city, Vietnam - Son, Le Van; Khanh, Pham Ngoc (Edelweiss Applied Science and Technology, 2025)
In the context of continuous and robust development of e-commerce, businesses are adjusting their return policies to meet the growing consumer demand, thereby increasing trust and enhancing the online shopping experience. The author of the study titled “The Impact of Return Policies on Consumers' Online Shopping Intentions in Ho Chi Minh City, Vietnam” aims to identify reimbursement factors that influence online shopping intentions through the mediating role of perceived service quality. The study measures the impact of these factors and offers governance implications to help businesses and retailers improve consumers' online shopping intentions. The research employs both qualitative and quantitative methods, collecting 303 valid questionnaires, which are analyzed using Structural Equation Modeling (SEM). The findings indicate that four factors positively influence consumers' online shopping intentions through the mediating role of intermediaries, listed in order: (i) reimbursement effort, (ii) reimbursement cost, (iii) exchange, and (iv) reimbursement period.